2012
DOI: 10.1051/0004-6361/201117927
|View full text |Cite
|
Sign up to set email alerts
|

Constraining Galactic cosmic-ray parameters withZ  ≤  2 nuclei

Abstract: Context. The secondary-to-primary B/C ratio is widely used for studying Galactic cosmic-ray propagation processes. The 2 H/ 4 He and 3 He/ 4 He ratios probe a different Z/A regime, which provides a test for the "universality" of propagation. Aims. We revisit the constraints on diffusion-model parameters set by the quartet ( 1 H, 2 H, 3 He, 4 He), using the most recent data as well as updated formulae for the inelastic and production cross-sections. Methods. Our analysis relies on the USINE propagation package … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(109 citation statements)
references
References 99 publications
2
106
0
1
Order By: Relevance
“…An initiative to improve them is described by Moskalenko (2011). A new treatment of the complicated processes involving the light (Z≤ 2) nuclei is given in Coste et al (2012), including for example Deuterium production by p-p fusion reactions. Antiproton production physics also requires improvements to take advantage of current and future data (Kappl & Winkler 2014).…”
Section: Advances In Propagation Modelsmentioning
confidence: 99%
“…An initiative to improve them is described by Moskalenko (2011). A new treatment of the complicated processes involving the light (Z≤ 2) nuclei is given in Coste et al (2012), including for example Deuterium production by p-p fusion reactions. Antiproton production physics also requires improvements to take advantage of current and future data (Kappl & Winkler 2014).…”
Section: Advances In Propagation Modelsmentioning
confidence: 99%
“…These parameter sets result from a secondaryto-primary ratio analysis (Maurin et al 2001) where 26 data points of the boron-to-carbon (B/C) ratio were fitted over the energy range from 0.1 to 35 GeV/n leading to a χ 2 less than 40. The advantage of choosing this study over more recent studies (Putze et al 2010;Coste et al 2012;Trotta et al 2011) J1745 − 3040…”
Section: The Effect Of Cosmic Ray Propagation Uncertaintiesmentioning
confidence: 99%
“…Although the program is already very complete and contains many physical processes and cross sections, some may be missing, incomplete, or obsolete for specific species. The study of hydrogen and helium isotopes has been shown to be as constraining on propagation models and parameters as the widely used Boron-to-Carbon ratio [14]. Cosmic-ray 2 H and 3 He are mostly secondary particles mainly produced after interactions of 1 H through fusion interaction (for 2 H) and 4 He through fragmentation (for 2 H and 3 He) in the interstellar medium.…”
Section: Introductionmentioning
confidence: 99%